1976
DOI: 10.1177/014616727600200220
|View full text |Cite
|
Sign up to set email alerts
|

Opportunity for Interaction as Reinforcement in a T-maze

Abstract: Two forms of handling were used as reinforcement in a T-maze for 34 albino rats. In a twelve-day experiment, those receiving gentling learned to avoid reinforcement while those receiving fondling learned to obtain it. In a six-day follow-up, rats were given either a fondling hand or a rat companion as reinforcement.The proportion of reinforced trials and running times were similar for both objects. Rats learned a task to obtain interaction with a rat or responsive surrogate. Werner and Latan6 (1974) have argu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
1

Year Published

1988
1988
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 6 publications
0
16
1
Order By: Relevance
“…Our results and similar ones reported by Werner and Anderson (1976) are in direct conflict with much of the "gentling" literature mentioned above. Collectively, they suggest that although some forms of human-rat interaction may be aversive to the rat, there are at least some interactions between human and rat that are positive enough to modify the rat's behavior in the absence of conventional food reward.…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…Our results and similar ones reported by Werner and Anderson (1976) are in direct conflict with much of the "gentling" literature mentioned above. Collectively, they suggest that although some forms of human-rat interaction may be aversive to the rat, there are at least some interactions between human and rat that are positive enough to modify the rat's behavior in the absence of conventional food reward.…”
contrasting
confidence: 99%
“…In one such study (Werner & Latane, 1974), an experimenter's hand movements attempted to simulate rats at play by "poking, lifting, rubbing and scratching, tapping and tumbling." These researchers concluded that contact with the human hand was as attractive as contact with another rat, thereby suggesting that a human-rat interaction can be a preferred activity (Werner & Anderson, 1976;Werner & Latane, 1974).…”
mentioning
confidence: 99%
“…Initiation of drug taking nearly always occurs in a social context in which peers provide social reward for the behavior, yet surprisingly little research has been conducted with animal models to investigate the influence of social interactions at the time of drug taking (i.e., social context). The presence of a nonthreatening conspecific is highly salient and rewarding, especially in adolescent rats (Vanderschuren et al, 1997;Spear, 2000); for instance, nonthreatening conspecifics 1) elicit approach (Panksepp et al, 1984), 2) elicit ultrasonic vocalizations thought to be indicative of positive affect (Burgdorf et al, 2008), 3) are positive reinforcers (Angermeier et al, 1959;Werner and Anderson, 1976;Evans et al, 1994), and 4) produce CPP (Calcagnetti and Schechter, 1992;Crowder and Hutto, 1992;Douglas et al, 2004). Research examining drug effects in a social context suggests that this is an important variable that influences sensitivity to the rewarding effects of drugs.…”
Section: Psychosocial Influences and Abused Drugsmentioning
confidence: 99%
“…Although Maurer et al (2008) reported that use of their gentling technique reduced the fear of laboratory rats towards humans, it is not clear which aspects of the procedure had the most impact on fear reduction. Other studies have indicated aversive responses, or absence of effects, when some of these techniques were used individually (e.g., Brudzynski and Ociepa, 1992;Burgdorf and Panksepp, 2001;Cloutier and Newberry, 2008;Werner and Anderson, 1976). Furthermore, provision of food treats is contraindicated in some studies due to conflict with research objectives, and is not always effective in mitigating the stressfulness of procedures (Cloutier and Newberry, 2008).…”
Section: Introductionmentioning
confidence: 99%